2020
DOI: 10.48550/arxiv.2010.14325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributed Optimization with Quantization for Computing Wasserstein Barycenters

Abstract: We study the problem of the decentralized computation of entropy-regularized semidiscrete Wasserstein barycenters over a network. Building upon recent primal-dual approaches, we propose a sampling gradient quantization scheme that allows efficient communication and computation of approximate barycenters where the factor distributions are stored distributedly on arbitrary networks. The communication and algorithmic complexity of the proposed algorithm are shown, with explicit dependency on the size of the suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Starting with [8,9] it was observed that decentralized methods with dual oracle are well suited for the WB problem. In the cycle of subsequent papers [9][10][11][12][13] different decentralized accelerated (randomized) algorithms were proposed for dual WB problem. In [20] the authors propose to reformulate the WB problem as a bilinear saddle-point problem (SPP).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Starting with [8,9] it was observed that decentralized methods with dual oracle are well suited for the WB problem. In the cycle of subsequent papers [9][10][11][12][13] different decentralized accelerated (randomized) algorithms were proposed for dual WB problem. In [20] the authors propose to reformulate the WB problem as a bilinear saddle-point problem (SPP).…”
Section: Related Workmentioning
confidence: 99%
“…If communication network changes over time, then the affine-consensus constraints also change over time, and so does the dual problem. This essentially requires to solve a family of dual problems, which is not possible by the accelerated gradient methods or the Mirror-Prox algorithm as in [9][10][11][12][13][14].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that it is possible to obtain accelerated primal-dual methods [195,196,199,200,201,202,203,204,155,205,132,206]. In particular, this allows to obtain improved complexity bounds for different types of optimal transport problems [202,207,205,140,208,209,210,211,212].…”
Section: Smooth Minimization Of Non-smooth Functionsmentioning
confidence: 99%
“…. , 𝜇 𝑁 are unknown with sample access, and develop stochastic optimization algorithms for approximating a Wasserstein barycenter with fixed support; see, e.g., [Claici, Chien, and Solomon, 2018, Staib, Claici, Solomon, and Jegelka, 2017, Krawtschenko, Uribe, Gasnikov, and Dvurechensky, 2020, Zhang, Qian, and Xie, 2023. Recently, numerical methods for continuous Wasserstein barycenter based on neural network parametrization or generative neural networks have been developed; see, e.g., [Cohen et al, 2020a, Fan, Taghvaei, and Chen, 2020, Korotin, Egiazarian, Li, and Burnaev, 2022, Korotin, Li, Solomon, and Burnaev, 2021, Li, Genevay, Yurochkin, and Solomon, 2020.…”
Section: Related Workmentioning
confidence: 99%